Unequivocal Detection of Solar Ultraviolet Radiation 250-300 nm (UV-C) at Earth’s Surface - Hoisington, Raymond D.; Whiteside, Mark; Herndon, J. Marvin (European Journal of Applied Sciences, 2023)
The toxicity of ultraviolet radiation in wavelength range 100-280 nm (UV-C) is well documented. UV-C irradiation can cause skin cancer, premature aging, visual problems and blindness. Prolonged exposure to UV radiation can kill both plants and animals, including entire forests. There are numerous assertions in the medical, public health, and geoscience literature that no UV-C reaches Earth’s surface, despite several studies to the contrary including one in 2007 by NASA. Naysayers blame technical problems such as stray light. Low-level UV-C measurements are difficult, if not nearly impossible, when using low integration values in the CCD Imaging Spectral Radiometers. This is due to the instrument’s internal and external atmospheric stray light issues, issues which even occur during calibration procedures that employ heated filament or gas-filled lamps. To obviate these inherent problems, one of us (RDH) designed, engineered, and constructed a Double Monochromator utilized in conjunction with the ILT950UV Spectral Radiometer operating in the raw data mode. Each of the initial measurements of solar irradiance displayed evidence of UV-C arriving at Earth’s surface, not high in the mountains, but just 176 meters above sea-level. These data were taken in the raw data mode, corrected for prism loss, with instrument noise, i.e. machine errors, subtracted. The non-zero value for relative spectral irradiance clearly shows the existence of UV-C at Earth’s surface, in the range 250-300 nm, even when measured under less than optimum atmospheric conditions. Research and development continue. We must know with certainty the condition of the stratospheric ozone layer that shields surface life from solar UV-C. Covert geoengineering atmospheric particulate pollution, in combination with industrial pollution of the atmosphere, is killing Earth’s stratospheric ozone layer. If unabated, it will sound the death knell for much of life on Earth.